Implementation of Sustainable Supply Chains for Oil Palm Industry in West Kalimantan - indriani, ika kurnia (Basic and Applied Accounting Research Journal, 2025)
This research aims to understand how palm oil companies can improve sustainable performance through effective supplier relationship strategies. The population to be used in this study is those who know the material studied and have worked in the palm oil industry. The method used in this study is the literature review method. Through the literature review, we also see the difference between sustainable and conventional practices in the palm oil industry. The results show, among others, that sustainable supply chain management is described by the process or system of palm oil management. In achieving success in sustainable supplier relationship management, the selection of supplier criteria should not only focus on economic criteria but also cover all aspects of the triple bottom line. This certification program is important for product continuity because it is the main thing in implementing the palm oil supply chain. The palm oil industry has also shown a high commitment from suppliers and palm oil companies to manage the sustainability risks between the two.